New poisson quadratic stochastic operator generated by 2-partition - Mohd Fadzullah, Nur Alis Aqeelah; Hamzah, Nur Zatul Akmar (Department of Computational and Theoretical Sciences, Kulliyyah of Science, IIUM, 2023)
The theory of quadratic stochastic operator (QSO) has been introduced by Bernstein in 1924 when he presented about population genetics. The research on QSO is still ongoing as there are various classes, conditions and measures that have not yet been studied by researchers. In this paper, we introduce a new class of Poisson QSO generated by 2-partition defined on set of all integers state space. We illustrate trajectory behaviour of the constructed QSO by cases. Lastly, we show that it is a regular transformation for some values of parameters.